Povoamento Pré-histórico da área de Pavia - Rocha, Leonor (2010)
The following article presents data resulting from a series of field surveys that were undertaken in the area of Pavia (Mora, Portugal) in recent years. During these field activities it was possible to identify a significant number of small settlements. This allowed us to create a chronological-cultural sequence for the area, and to pose several important questions concerning its evolution.